On the issue of software for environmental information systems - Gonchar Daria; Nikulinа Svetlana; Fateeva Natalia; Belova Joanna; Vasyukov Alexander; Tishchenko Ksenia (E3S Web of Conferences, 2024)
The increase in the number of sources of pollutants into the atmospheric air is one of the largest environmental problems in the modern world. In order to control emissions of harmful substances, calculations of maximum permissible concentrations of pollutants are used. Calculations of emission sources and maximum permissible concentrations are quite complex, and it is impractical to carry them out manually, since the calculation process takes a lot of time, while there is a high probability of errors. To simplify such a task, special software tools are used – unified programs for calculating atmospheric pollution (UPRZA). The article is devoted to the issues of increasing the level of automation of calculations of emission sources and maximum permissible concentrations using UPRZA. The issues of the standard structure of the UPRSA are considered, input parameters, algorithms for calculating the parameters of the emission source and maximum permissible concentrations are determined in accordance with the methods used. Methods of increasing the level of automation are proposed. The analysis of possible ways of development of these software complexes is carried out. The article describes the process of developing a unified program for calculating atmospheric pollution, the main advantages of its application.